Jeremiah and God's plans of well-being - Green, Barbara, 1946- (Columbia, South Carolina University of South Carolina Press, 2013)
"In Biblical Jeremiah, Barbara Green explores the prophet Jeremiah as a literary persona of the biblical book through seven periods of his prophetic ministry, focusing on the concerns and circumstances that shaped his struggles. Having confronted the vast complexity of scholarly issues found in the Book of Jeremiah, Green has chosen to examine the literary presentation of the prophet rather than focus on the precise historical details or the speculative processes of composition. What Green exposes is a prophet affected by the dire circumstances of his life, struggling consistently, but ultimately failing at his most urgent task of persuasion."--book jacket
Chart of the book of Jeremiah assumed -- Introduction: Scope and stipulations -- Womb and workshop : Jeremiah learns his calling : chapters 1, 46-51 -- Overture : problems and resolutions rehearsed : chapters 2-10 -- Resistance : deity and prophet as partners and adversaries : chapters 11-20 -- Deep learning : experiencing the heart of God : chapters 11-20 -- Well-being or disaster : the case argued : chapters 21-39 -- God's desires contested : the case embodied by strange resemblance and in negative space : chapters 21-45, 52 -- Getting out : chapters 30-33, 24, 26, 29 -- Afterword and implications
Includes bibliographical references (pages 205-211) and index
Keywords: Jeremiah -- (Biblical prophet); Bible. -- Criticism, interpretation, etc; Criticism, interpretation, etc